Fluorescent labelling in living dental pulp stem cells by graphene oxide quantum dots. Issue 1 (4th December 2019) - Li, Xincong; Guo, Haowei; Ren, Shuangshuang; Fan, Ruirui; Yu, Yijun; Zhang, He; Liu, Chao; Miao, Leiying
Abstract: Cellular labelling is possible to offer significant information after transplantation for the purpose of determining stem cell therapy's efficacy. According to the research, it has been reported that graphene oxide quantum dots (GOQDs) are a kind of healthy biological labelling agent for stem cells which show little cytotoxicity. GOQDs' interactions have been examined on the dental pulp stem cells (hDPSCs) of human beings for the purpose of investigating GOQD's biocompatibility and uptake and explored GOQDs' effects on hDPSCs' metabolic activity and the proliferation. According to the outcomes, GDQDs have been accepted by hDPSCs in a time-dependent and concentration-dependent behaviour. Moreover, no important changes have been discovered within hDOPSCs' proliferation, viability as well as metabolic activity after treatment with GOQDs. Therefore, such resources have shown that GOQDs can be multifunctional agents for cell therapy, drug delivery as well as cell imaging and also as outstanding candidates for labelling stem cells.